Multilevel Analysis on the Factors Associated with Low Birth Weight in Temanggung, Central Java - Khayati, Yulia Nur; Prayitno, Adi; Poncorini, Eti (Journal of Maternal and Child Health, 2016)
Background: Infants with low birth weight or LBW is one of the risk factors for infant mortality. Complications LBW actually can be prevented and dealt with, but is constrained by access to health care, socio-economic circumstances, a referral system that has not gone well, delays in early detection and awareness of parents to seek medical help. By looking at the number of deaths caused by LBW remains high, and research on the causes of LBW widely used partial analysis, and have not been analyzed in stages, the researchers conducted this research with multilevel analysis.Subjects and Method: This was an observational studt with case control design. A total sample of 120 infants were selected by fixed disease sampling with a ratio of 1: 2 between cases and controls. Data were analyzed using multiple logistic regression.Results: There are three variables at the individual level were significantly associated with LBW and was statistically significant can among others, motherÃ¢â¬â¢s education (OR= 0.19; 95% CI= 0:07 to 0.53; p= 0.001), history of ANC t (OR= 7.76; 95% CI= 2.18 to 27.62; p= 0.002) and the nutritional mother status (OR= 5.61; 95% CI= 0.21 to 0.79; p= 0.008) and the variables that are not statistically significant is the motherÃ¢â¬â¢s age and family income, and there are ÃÂ no contextual role within house with wellness facilities with LBW expressed by ICC < 0.001.Conclusion: The influence of maternal education, a history of the ANC examination and nutritional status of mothers with LBW and there is no contextual role of distance between home and health care facilities with LBW. This study suggests to health professional to improve the coverage of the ANC.Keywords: multilevel analysis, factor low birth weightCorrespondence: Yulia Nur Khayati. School of Health and sciences, STIKes Ngudi Waluyo, Ungaran, Indonesia. Email: yulia.farras@gmail.com.Journal of Maternal and Child Health (2016), 1(1): 7-12https://doi.org/10.26911/thejmch.2016.01.01.02